Subpopulation contributions to a breeding metapopulation of migratory arctic herbivores: survival, fecundity and asymmetric dispersal. Issue 7 (18th May 2022) - Alisauskas, Ray T.; Calvert, Anna M.; Leafloor, James O.; Rockwell, Robert F.; Drake, Kiel L.; Kellett, Dana K.; Brook, Rodney W.; Abraham, Kenneth F.
Abstract : Estimates of demographic parameters for lesser snow geese Anser caerulescens caerulescens have become critical to understand ecosystem change in northern Canada. Exponential increase in abundance has produced hyperdensities of these herbivores that can affect Arctic ecosystem stability through intense foraging. Increased and sustained marking of individually‐identifiable lesser snow geese over their breeding distribution now permits joint estimation of local vital rates and movement probabilities among widely scattered subpopulations. We used multi‐state models, including an unobservable state, with live captures from 5 subpopulations and dead recoveries to estimate annual probabilities of 1) survival, 2) capture, 3) reported mortality and 4) movement to other subpopulations, as well as derived estimates for probabilities of site fidelity and harvest. Our dataset included 144 719 captures of 139 177 lesser snow geese marked with metal legbands, from 2006 to 2015, of which 5542 were recaptured near breeding sites and 9709 were recovered dead in North America. The best model supported variation in survival by subpopulation and age, with additive effects of subpopulation, age and sex on movement probability. Male breeding dispersal was greater than by females, and juvenile geese were more likely to move than adults. Strong northeastward geographic asymmetry in the probability of breeding movement was consistent with an eastward shift in wintering distribution observed in hunter recoveries. Mean annual survival ranged from 0.79 to 0.94 for adults, and 0.16 to 0.47 for juvenile geese, with a strong negative relationship between regional adult and juvenile survival. Harvest probabilities were all ≤ 0.03 for adult and ≤ 0.06 for juvenile geese, suggesting little influence from direct anthropogenic exploitation. Metrics for subpopulation persistence and contributions of each to the metapopulation suggested declines in all but one subpopulation, and a declining Midcontinent population overall. Our study highlights the importance of all subpopulation demographic parameters as modulators of persistence at both local and range‐wide population dynamics.